IMPLEMENTASI MEDIA PEMBELAJARAN FISIKA BERUPA LKPD BERBANTUAN PHET SIMULATION PADA MATERI LISTRIK ARUS SEARAH - Lesmana Sidik, Endri; Marsela, Sherin; Rusdiana, Dadi (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2022)
Physics was one of the studies that had a wide range of abstract concepts and in order to understand those, all of the students need to involve their senses. Peth Simulation was a learning media equipped with LKPD guidelines that would help teachers to deliver the material efficiently. Therefore, this research had the purpose to evaluate the implementation of LKPD learning media using Phet Simulation in direct current electricity subject. The method used in this research was pre-experiment with data from pre-test and post-test questionnaires in google form delivered to eight samples and after that, the data would be processed by SPSS with wilcoxon calculation. The result of this research based on wilcoxon calculation was showing at sig. (two-tailed) = 0.010 < 0.5 so the hypothesis was accepted and proven that there was a significant influence with the implementation of LKPD learning media using Phet Simulation in direct current electricity subject.